A CRITICAL ANALYSIS OF PAKISTAN - AFGHAN RELATIONS (2017-2021): A CRITICAL ANALYSIS OF PAKISTAN - AFGHAN RELATIONS (2017-2021) - Saeed, A. (Farabi Journal of Social Sciences, 2022)
Pakistan and Afghanistan share 2,260 kilometers. Though both the states are immediate neighbors, but since 1947, their relations remained fragile and have seen many ups and downs. However, this research is focused on Pakistan-Afghanistan relations during the Pakistan government (2017-2021) from a critical point of view. The era has witnessed some basic changes in the attitudes between the two countries towards each other. Pakistan abandoned its policy of strategic depth while Afghanistan and America realized that the road to peace, stability and prosperity goes through Pakistan. Though the dialogue and talks did not succeed but it provided a base for future discussions. This study critically analyzes the relations between the two countries in the given period of time from different dimensions: political, economic, social, and strategic etc. Though the relations of Pakistan and Afghanistan did not remain ideal from the day first but there are some common areas where they can co-operate the convergence of interest while there are also other areas where their interests contradict, the divergence of interest. However, the study finds that the convergence points are more than the divergence but the countries failed in building durable trust. The problems started from disagreement on Durand Line and then the chain of events and issues stretched to the current war against militancy and peace process in Afghanistan. During the under-discussion era, trade and cooperation increased between Pakistan and Afghanistan. In this respect, this article shows that the development of Pak-Afghan relations is somewhat like one step forward and two steps backwards. Keywords: state, peace, terrorism, relations, Afghanistan, Pakistan, stability, war, security.